Pelaksanaan dan Hasil Belajar Merajut pada Program Keaksaraan Fungsional di Pkbm Farilla Ilmi Kota Padang - Nola Petri Soliza, Avia; Irmawita, Irmawita (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is based on the knitting learning program plan at PKBM Farilla Ilmi. This is evidenced by the completeness of learning suggestions, getting the interest of learning citizens, the attention of learning citizens and the implementation of good learning activities. The purpose of this study is to discuss the implementation of learning to knit in PKBM Farilla Ilmi based on methods, materials, media and evaluation. This type of research is quantitative descriptive. The population in this study replaced 20 people and a sample of 10 people who were determined based on the saturation sampling method. The technique of collecting data uses questionnaires and data analysis uses percentage formulas. The results of this study indicate that: The method of implementing learning is categorized very well, learning material is categorized very well, learning media are categorized very well and learning is categorized very well. The suggestion from this research is that the organization can maintain and improve the implementation of learning for the better.